2017
DOI: 10.11646/phytotaxa.317.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative morphological evidence for recognition of a new species within Ceratozamia (Zamiaceae) from Mexico

Abstract: Several Ceratozamia populations from the “Carso Huasteco” region in Mexico have a controversial circumscription and have been historically identified as Ceratozamia fuscoviridis. In this paper, we present a review of the taxonomic history of this species and provide taxa circumscriptions based on analyses of herbarium specimens from this region and supplemented with fieldwork. For this, we have studied qualitative and quantitative morphological variation at population level. We recognize two species in this gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Species diagnoses in Zamia have traditionally been based on vegetative characteristics (Stevenson 1981, 2001, Nicolalde-Morejón et al 2008, Martínez-Domínguez et al 2017a, b, 2018, due to the absence of reproductive structures in herbarium specimens. However, some characters states of these structures are crucial for identification, and Zamia is no exception (Stevenson 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Species diagnoses in Zamia have traditionally been based on vegetative characteristics (Stevenson 1981, 2001, Nicolalde-Morejón et al 2008, Martínez-Domínguez et al 2017a, b, 2018, due to the absence of reproductive structures in herbarium specimens. However, some characters states of these structures are crucial for identification, and Zamia is no exception (Stevenson 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Criteria to delimit species. The taxonomic treatment presented here is partly based on our previously published work on species complexes, considered from an integrative taxonomy perspective for corroboration or refutation of taxonomic hypotheses and employing the “taxonomic circle” sensu DeSalle et al (2005) , in which multiple data sources are analyzed independently for hypotheses testing ( Martínez-Domínguez et al 2016 ; 2017a , b , 2018a , 2020 , 2022a , b ). For taxa we have not treated previously, species were recognized by a unique combination of morphological characters evaluated at the population level, considering their biogeographic distribution patterns as an additional source of evidence.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Etymology. The specific epithet is in honor of Charles Joseph Chamberlain in recognition of his remarkable contributions to knowledge of the biology of the cycads and his fieldwork on Mexican Cycads (Martínez-Domínguez et al 2017a).…”
Section: Ceratozamia Brevifronsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other contemporary studies have shown that these characters can be highly variable between and amongst populations, which limits species diagnosis (Martínez-Domínguez et al 2016; 2017a, b, c). Other characters commonly used are the direction, form and texture of leaflets and the formation of prickles (Pérez-Farrera et al 2001; Vovides et al 2003).…”
Section: Introductionmentioning
confidence: 99%